Financial reforms in Eastern Europe : a policy model for Poland - Gupta, Kanhaya L. (Kanhaya Lal), 1935- (Routledge studies of societies in transition., 1998)
This book presents a valuable model for simulating the effects of financial reforms in transitional economies. Poland is used as a case study to show the effectiveness of the variety of policy simulations offered by this model.